THE USE OF THE PHONICS METHOD IN LITERACY - de Lourdes Andrade Jovial Macarini, Sandra (Revista Gênero e Interdisciplinaridade, 2026)
This article proposes a reflection on the use of the phonics method in the literacy of children in the early grades of elementary school, discussing its theoretical foundation, effective scientific evidence, and the challenges of its implementation in Brazilian school contexts. The new literature review reveals that the phonics method benefits the development of phonological awareness and decoding skills and is widely recommended in international educational policies. However, its successful use requires consistent teacher training and a connection with literacy practices that demand understanding and social use of reading and writing. It is believed that the phonics method, when combined with literacy practices, becomes an active strategy for comprehensive literacy.